Mid-to-Late Holocene Aboriginal Flaked Stone Artefact Technology on the Cumberland Plain, Sydney, New South Wales, Australia: A View from the South Creek Catchment. (2nd October 2018) - McLaren, Andrew P.; Oakes, G.; Atkinson, L.; Jordan, D.; Toms, Phil S.
ABSTRACT: Despite being one of the most intensively investigated archaeological regions in Australia, the flaked stone technologies employed by Aboriginal people occupying the Cumberland Plain of western Sydney, New South Wales, remain poorly documented in the published literature. Here we present and discuss the results of a technological analysis of a sizeable cultural lithic assemblage recovered from a compliance-based salvage excavation completed within Woorong Park Residual Rise 1, an open air Aboriginal archaeological site located in the northwestern portion of the Plain, in the South Creek catchment. The flaked stone technology evidenced by this assemblage is characterized through descriptions of observed raw materials, reduction techniques and methods, flake attributes and tool types. The behavioral implications of the assemblage are considered in light of the region's existing archaeological dataset and with particular reference to McDonald's [(2008). Dreamtime superhighway: Sydney Basin rock art and prehistoric information exchange (Terra Australis 27). Canberra: Australian National University Press] comprehensive behavioral land use model for the broader Sydney region, which wholly encompasses the Cumberland Plain.